A high-mobility group box 1 that binds to DNA, enhances pro-inflammatory activity, and acts as an anti-infection molecule in black rockfish, Sebastes schlegelii. (September 2016) - Xin-peng, Zhao; Yong-hua, Hu; Yong, Liu; Jing-jing, Wang; Guang-hua, Wang; Ren-jie, Wang; Min, Zhang
Abstract: High-mobility group box (HMGB) 1 is a chromosomal protein that plays critical roles in DNA transcription, replication and repair. In addition, HMGB1 functions as a pro-inflammatory molecule in many vertebrates and invertebrates. In teleosts, very limited studies of HMGB1 have been reported. In this study, we identified a HMGB1 homologue (SsHMGB1) from black rockfish ( Sebastes schlegelii ) and analyzed its structure, expression and biological function. The open reading frame of SsHMGB1 is 621 bp, with a 5'-untranslated region (UTR) of 62 bp and a 3′-UTR of 645 bp. SsHMGB1 contains two typical HMG boxes and an acidic C-terminal tail. The deduced amino acid sequence of SsHMGB1 shares the highest overall identity (89.4%) with the HMGB1 of Anoplopoma fimbria . The expression of SsHMGB1 occurred in multiple tissues and was highest in the brain. Moreover, the mRNA level of SsHMGB1 in head kidney (HK) macrophages could be induced by Listonella anguillarum in a time-dependent manner. Recombinant SsHMGB1 purified from Escherichia coli (i) bound DNA fragments in a dose-dependent manner; and (ii) induced the expression of cytokines in HK macrophages, including a significant increase in TNF-α activity and enhanced mRNA level of TNF13B and IL-1 β, which are known to be involved in antibacterial defense; moreover, (iii) significantly improved the macrophage bactericidal activity together with reduced pathogen dissemination and replication of bacteria in fish kidney. These results indicated that SsHMGB1 is a novel HMGB1 that possesses apparent immunoregulatory properties and is likely to be involved in fighting bacterial infection. Highlights: A HMGB1 homologue (SsHMGB1) was identified and characterized. Expression of SsHMGB1 in macrophages could be induced by Listonella anguillarum. Recombinant SsHMGB1 purified from E. coli was able to bind with DNA fragments. Recombinant SsHMGB1 possesses apparent immunoregulatory property and is likely to be involved in anti-bacterial infection.